Use of Cesarean Birth among Robson Groups 2 and 4 at Mizan-Tepi University Hospital, Ethiopia - Margo S. Harrison; Tewodros Liyew; Ephrem Kirub; Biruk Teshome; Andrea Jimenez-Zambrano; Margaret Muldrow; Teklemariam Yarinbab (Obstetrics and Gynecology International)
Background. Primary cesarean birth rates were high among women who were either nulliparous (Group 2) or multiparous (Group 4) with a single, cephalic, term fetus who were induced, augmented, or underwent cesarean birth before labor in our study cohort. Objectives. The objective of this analysis was to determine what risk factors were associated with cesarean birth among Robson Groups 2 and 4. Methods. This study was a prospective hospital-based cross-sectional analysis of a convenience sample of 1,000 women who delivered at Mizan-Tepi University Teaching Hospital in the summer and fall of 2019. Results. Women in Robson Groups 2 and 4 comprised 11.4% (n = 113) of the total population (n = 993). The cesarean birth rate in Robson Group 2 (n = 56) was 37.5% and in Robson Group 4 (n = 57) was 24.6%. In Robson Group 2, of all prelabor cesareans (n = 5), one birth was elective cesarean by maternal request; the intrapartum cesarean births (n = 16) mostly had a maternal or fetal indication (93.8%), with one birth (6.2%) indicated by “failed induction or augmentation,” which was a combined indication. In Robson Group 4, all 4 women delivered by prelabor cesarean had a maternal indication (one was missing data), and 3 of the intrapartum cesareans were indicated by “failed induction or augmentation.” In multivariable modeling of Robson Group 2, having a labor duration of “not applicable” increased the risk of cesarean delivery (RR 2.9, CI (1.5, 5.4)). The odds of requiring maternal antibiotics was the only notable outcome with increased risk (RR 11.1, CI (1.9, 64.9)). In multivariable modeling of Robson Group 4, having a labor longer than 24 hours trended towards a significant association with cesarean (RR 3.6, CI (0.9, 14.3)), and women had a more dilated cervix on admission trended toward having a lower odds of cesarean (RR 0.8, CI (0.6, 1.0)). Conclusion. Though rates of primary cesarean birth among women who have a term, single, cephalic fetus and are induced, augmented, or undergone prelabor cesarean birth are high, those that occur intrapartum seem to be associated with appropriate risk factors and indications, though we cannot say this definitely as we did not perform an audit. More research is needed on the prelabor subgroup as a separate entity.